Об устойчивости стационарных вращений динамически симметричного твердого тела на струнном колеблющемся подвесе - Слынько, В.И. (Видавничий дім "Академперіодика" НАН України, 2008)
The equations of movement are introduced, and the stability of stationary movements of a solid body on the oscillating string suspension is investigated.